OP0083 Temporal trends and mortality of hospitalisedpatients with adult onset stills disease: a nationwide estimate. (12th June 2018) - Mehta, B; Briggs, W.; Efthimiou, P.
Abstract : Background: There is a dearth of epidemiological studies on Adult Onset Still's Disease (AOSD). Majority of studies are from single centres or are regional. The largest AOSD epidemiological study till date describes 512 patients. 1 Objectives: To describe the demographics, complications, mortality and trends of hospitalised patients with AOSD in United States. Also, to understand the factors associated with mortality in these patients. Methods: All adult (>18 years) hospitalised patients between 2009 and 2013 from a nationwide inpatient sample (NIS) database were captured. AOSD patients were identified using the ICD-9 code 714.2. Patients also coded for Rheumatoid Arthritis, Lupus, Myositis, Polymyalgia Rheumatica, Ankylosing Spondylosis and Psoriatic Arthritis were excluded. This was done in order to capture patients with strictly AOSD. NIS is the largest all-payer inpatient care database in the United States with approximately 8 million hospitalizations each year. Discharge weights were used to enable nationwide estimates. Descriptive statistics were represented as means/medians for continuous and as frequencies and percentages for categorical variables. A survey weighted logistic regression model was used to describe the associations with in-hospital death. Results: Between 2009 and 2013, 5, 820 AOSD patients were hospitalised (table 1). AOSD patients had a mean age of 53.6 (SE – 0.61) years, 3817 (65.6%) were females. The racial/ethnic distribution showed that 56% white, 15% African American, 11.7% Hispanic and 3% Asian patients were affected. Over the years, the number of white patients that are hospitalised seems to have increased. 37.6% were hospitalised in urban teaching hospitals. 100 (1.7%) of patients developed Macrophage Activating Syndrome (MAS). 66 (1.1%) patients had disseminated intravascular coagulation (DIC) and 25 (0.4%) had thrombotic thrombocytopenic purpura (TTP). Mean length of stay was 6.9 days. There were 154 inpatient deaths in 5 years (mortality 2.6%). The patients who died in the hospital had a higher mean age of 62.4 (SE- 3.1) years, had a higher proportion of Asians (13.9%) and had increased number of comorbid conditions. Asians had 6.4 times the risk of in-hospital death compared to Whites. The risk for in-hospital death is 30 times higher if a AOSD patient had concurrent DIC. Conclusions: In hospitalised American AOSD patients, the average age was higher than previously described in cross sectional studies. This may indicate an ageing population with a higher number of comorbidities that justify hospitalisation. More patients were in large or urban teaching hospitals compared to small or rural hospitals. In-hospital death was associated with increased comorbid conditions and was significantly higher among Asians and patients with DIC. To our knowledge, this is the largest epidemiological study of AOSD. Reference: [1] Sakata N, et al. Rheumatol Int2016;36(10):1399–405. doi:10.1007/s00296-016-3546-8 Disclosure of Interest: None declared